Pendidikan Kesehatan Sebagai Upaya Peningkatkan Pengetahuan Pencegahan Stunting pada Perempuan Pesisir - Astyandini, Budi; Khobibah; Dewanto, Icsan Rizqi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Coastal women are a vulnerable group economically and knowledgeably due to educational and cultural limitations that do not support health. The causes of stunting in toddlers begin with wedding preparations, pregnancy to toddlerhood. Knowledge about stunting prevention contributes to the high number of stunting cases in coastal areas. Health education through counseling and education is the right method to be developed according to the needs and conditions of coastal women. The purpose of improving the knowledge and behavior of coastal women in the pre-marriage, pregnant and those with toddlers includes understanding, parenting, and fish-based diets to prevent stunting. The community service method is carried out by providing counseling and education directly on the target of knowledge assessed before and after 3 months of activities. The results of the activity were obtained from 20 mothers-to-be, pregnant women, mothers under five and KPPI members who were given differences before and after being given health education with a p value of 0.00. Improvement at the time of posttest. The Paired t Test for differences in knowledge before and after receiving health education obtained a significant calculation value of 0.000 < 0.005 which shows a difference in knowledge before and after being given health education about stunting prevention with a standard deviation of 1.495 with data at the lower limit of 4.041 and the upper limit of 3.484. Conclusion of health education to increase the knowledge of coastal women in Biru sari, Kalibuntu Village, wetan Kendal. It is hoped that a coastal women's group will be formed that is able to prevent stunting.